Coadministration of VDR and RXR agonists synergistically alleviates atherosclerosis through inhibition of oxidative stress: An in vivo and in vitro study. (August 2016) - Lin, L.M.; Peng, F.; Liu, Y.P.; Chai, D.J.; Ning, R.B.; Xu, C.S.; Lin, J.X.
Abstract: Background and aims: Diabetes contributes to atherosclerosis partially through induction of oxidative stress. Both vitamin D receptor (VDR) and retinoid X receptor (RXR) agonists exhibit anti-atherogenic effects. Methods: We explored the effects of combination treatment with VDR and RXR agonists (represented by calcitriol and bexarotene, respectively) on atherosclerosis progression and the mechanisms involved, using a diabetes model of mice. The animals were intragastrically fed calcitriol (200 ng/kg, twice-a-week), bexarotene (10 mg/kg, once-daily) either alone or in combination for 12 weeks. Results: VDR and RXR agonists delayed atherosclerosis progression independent of serum lipid and glucose levels, and significantly reduced the protein expression of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunit gp91phox and nuclear factor-kappa B (NF-κB) subunit p65, as well as plasma biomarkers of oxidative stress and inflammation. Combination therapy alleviated atherosclerosis and inhibited indexes of oxidative stress and inflammation to a greater extent than either monotherapy. In the in vitro study, naturally occurring VDR ligand 1α, 25-dihydroxyvitamin D3 (1, 25[OH]2 D3 ) and RXR ligand 9-cis retinoic acid (9-cis-RA), both significantly inhibited high-glucose-induced endothelial cell apoptosis. Co-administration of VDR and RXR ligands produced synergistic protection against endothelial apoptosis by antagonizing the protein kinase C /NADPH oxidase/reactive oxygen species pathway. The inhibitory effects of 9-cis-RA on oxidative stress was attenuated when VDR was downregulated by VDR siRNA; however, downregulation of RXR by RXR siRNA imposed no influence on the effects of 1, 25(OH)2 D3 . Conclusions: Combination treatment with VDR and RXR agonists synergistically alleviated diabetic atherosclerosis through inhibition of oxidative stress, and the preventive effects of RXR agonist may partially depend on VDR activation. Highlights: Coadministration of VDR and RXR agonists exerts synergistic protection against atherogenesis compared with either monotherapy. The protection correlates with additive suppression of endothelial apoptosis via inhibiting PKC/NADPH oxidase/ROS pathway. The endothelial protection effects by RXR agonist may in large part rely on VDR activation.